Efektivitas Komunikasi Program Optimalisasi Lahan Pekarangan - Restiawan Permana; Sarwititi Sarwoprasodjo; Djoko Susanto; Amiruddin Saleh (Jurnal Komunikasi Pembangunan, 2011)
Abstract For change and renewal in society, effectiveness communications is needed so as to produce a change in the rate of cognitive, affective, and conative. In the Kawasan Rumah Pangan Lestari (KRPL) program, effectiveness communications is absolutely essential for their future as a program participant is able to adopt and implement the optimalization of their backyards so as not to let it alone. The purpose of this study were to (1) analyze the effectiveness communications KRPL program in the Mulyasari Village Ciampel District Karawang of West Java, (2) analyze the relationship between individual characteristics variable and external factors variable to the effectiveness communications variable of KRPL program in the Mulyasari Village Ciampel District Karawang of West Java, and (3) analyze the relationship between the effectiveness communications variable of KRPL program with the optimalization of backyard variable in the Mulyasari Village Ciampel District Karawang of West Java. The study were designed to use quantitative survey methods explanation research. These results indicate that (1) KRPL program conducted in the Mulyasari Village District Ciampel Karawang of West Java is quite effective at the level of cognitive, affective, and conative. It is evident that most participants KRPL program can understand the information they get from the instructor of the program, they also want to implement this optimalization program of their backyards, and they also run the program from The Ministry of Agriculture in optimize their backyards that they have, (2) individual characteristics significantly and positively related to the effectiveness communication is an indicator of education and yard area. The external factor significantly and positively related to the effectiveness communication is an access to information, public policy, and the illumination intensity, and (3) effectiveness communications (cognitive, affective, conative) of KRPL program significantly and positively related to optimalization of their utilization backyards. Keywords: effectiveness communication, backyard optimization